Bussiness Model Canvas: Electric Coconut Scraper Machine / Norhafizah Ab Jalil - Ab Jalil, Norhafizah (2020)
Have you ever heard about an electric coconut scraper machine? Based on the research and observation, only a small amount of people acknowledge about the invention of this coconut scraper. Demand in market for coconut scraper is a stuff of legend since mostly Malayan food was using coconut milk. Common coconut scraper is traditionally difficult to use by family or small industries since they cannot produce maximum coconut milk because it take a long time for scraping the coconut meat from the coconut shell and turning into the coconut milk. Besides, the traditional method of getting coconut milk by using common coconut scraper is associated with numerous problems, such as time consuming, tediousness and unhygienic products. The idea came to the minds since a solution is now required, which is the very reason for composing this study and its following innovation process. There is a need to introduce a modern coconut scraper that will improve the quality and quantity of coconut milk production. I decided to invent an electric coconut scraper machine as my product. The electric coconut scraper machine is not like the other coconut scraper. I developed new special features and that makes it different from other coconut scraper so that it could be used by consumer coconut scraper with satisfaction. Among the features that is developed comes with stainless steel blade, hole at the bottom of the body, power button, the press button safety switch, rubber below the plastic body, plug with copper cable electric, full body plastic and holder. The electric coconut scraper machine is an improved product by making an adjustment or modification to the traditional coconut scraper that have only one function which is scrape the coconut meat with copper blade sharp